Sodium and potassium concentration in mangrove leaf as sublethal indicator of oil stress in mangrove trees, Taklong Island National marine Reserve (TINMAR), Nueva Valencia, Guimaras. - Yu, Amy April Amor Mata
This study involve the determination of total sodium and potassium in mangrove leaves using the flameatomic absorption spectroscopy (F-AAS), comparison of the sodium and potassiumconcentrations among species, between sites and sampling periods. Results show that mangroves in the oil-affected areas have high Na/K ratio in the leaves compared to the mangroves found in the control area. This observation reflects an impairment of the salt ((Na) exclusion mechanism in the mangrove trees as a result of oil pollution. Moreover,high Nas/K is observed in the first ssampling period than in the second samplingperiod indicating recovery of the mangroves from oil stress. Among the mangrove species studied, Avicennia marina in Brgy. Pototan and Sonneratia alba in Tandog Is. were the most vulnerable to the toxic effects of oil. These mangrove species are still exhibiting stress over the sampling period and were not able to recover from oil stress for almost one and a half years. The Na/K ratio approach to measure the physiologiccal health of mangrove trees at an oil spill site offers a potentially useful means of documenting oil stress and recovery from oil strees and recovery from oil stress in mangrove trees and also to other salt-excluding halphytes. Thus, the Na/K ratio can be used as sublethal indicator of oil stress in mangrove trees.